Notes & queries : Vol. 2. - Whitaker, Brian (London : Fourth Estate, 1991)
A collection of questions and their various answers from the readers of "The Guardian", such as: is it true that goldfish have a memory span of five seconds? When were elastic bands invented? Did Napoleon ever say "Not tonight Josephi
Includes index.